Desarrollo Turístico versus Calidad y Sustentabilidad Percibidas: Barrancas del Cobre, México - Manuel Ramón González Herrera; Vinod Sasidharan; Julián Alberto Álvarez Hernández (European Scientific Journal, ESJ, 2018)
The study of perceptions about tourism development at the Copper Canyon Park in Chihuahua, Mexico, is presented in order to assess the perceived quality and sustainability of the current model of territorial tourism development. A qualitative methodology by means of an explanatory and deductive approach was used, through which valid qualitative data were obtained, such as words and texts based on personal opinions of the hosts and visitors, which were obtained through surveys, interviews and online opinion. The sample was composed of residents from Creel, Divisadero, Urique and Otero, as well as tourists who have visited the destination. As result, the characterization of the tourist development of Copper Canyon Park is presented, as well as the study of local opinion regarding the tourism development model, and the analysis of visitors' perceptions. It is concluded that the projection of tourism development using the opinions of hosts and visitors is a necessary tool for the participatory management of quality and territorial sustainability of tourism.